Frailty and Kidney Disease A Practical Guide to Clinical Management - Musso, Carlos Guido; Jauregui, José Ricardo; Macías-Núñez, Juan Florencio; Covic, Adrian (Springer International Publishing, 2021)
This unique book reviews the information available in the literature regarding the new syndrome, frailty, in patients with various renal conditions, such as acute kidney injury, chronic kidney disease, as well as dialysis and transplant patients. The topic is of importance in nephrology, specifically nephrogeriatrics, since frailty is a condition affecting many elderly patients and which is becoming increasingly common in medical practice. As such, there is a considerable need for information to assist professionals treating these patients. The book includes chapters on the frailty syndrome (definition, evaluation and treatment), the main geriatric syndromes (gait disorder, falls, incontinence, and delirium), the main renal syndromes (acute renal injury, chronic kidney disease) as well as dialysis and kidney transplant, and the relationship between geriatrics and renal syndromes. Frailty and Kidney Disease: A Practical Guide to Clinical Management is an essential resource for general practitioners, researchers, internal medicine physicians, geriatricians, and nephrologists
Frailty Phenotype -- Gait Disorder -- Falls -- Immobility Syndrome -- Incontinence -- Interrelationship Between Geriatrics and Renal Syndromes -- Frailty Evaluation -- Frailty in Chronic Kidney Disease -- Frailty in Acute Kidney Injury -- Frailty in Chronic Dialysis -- Frailty in Kidney Transplant -- Palliative Care in Renal Disease
Keywords: Geriatrics; Nephrology